Decir lo normal. Reflexiones en torno al trasfondo ético del lenguaje de la psiquiatría - Maruy van den Broek, Rodrigo (2019)
This article aims to rethink the ethical dimensions of the psychiatric diagnosis as a speech act. Thereupon, we will explore the internal tensions of the psychiatric language in light of Kant’s distinction between determining and reflective judgements. Then, we shall emphasize the performative dimension of the diagnosis from the perspectives of Austin and Wittgenstein, thus problematizing the idea that it is an objective description of the patient’s abnormality. Finally, in dialogue with the epistemic injustice approach, we will propose a commissive notion of diagnosis that can also serve as a means for social criticism.